The Influence of Interpregnancy Interval and Iron Tablet Adherence on the Occurrence of Anemia Among Pregnant Women - Sudarmi, Sudarmi; Asih, Yusari; Purwaningsih, Dewi; Nurlaila, Nurlaila; Pranajaya, R (Poltekkes Kemenkes Tanjung Karang, 2025)
Anemia in pregnancy is a significant public health concern that contributes to maternal morbidity, adverse pregnancy outcomes, and neonatal complications. This study aimed to analyze the effects of the interpregnancy interval and adherence to iron–folic acid (IFA) tablet use on the incidence of anemia among pregnant women. A cross-sectional analytic survey was conducted in Tanjung Sari District, Lampung, Indonesia, involving 114 pregnant women selected through purposive random sampling from a total population of 334, including pregnant women aged 18–45 years in the first or second trimester, with at least one previous pregnancy, complete ANC records, and willingness to participate. Data were collected through structured questionnaires, anthropometric measurements, and documentation review. Anemia was assessed based on hemoglobin levels, while interpregnancy interval and IFA adherence were measured using standardized tools. Bivariate analysis was performed using the chi-square test, and multivariate analysis employed logistic regression to identify predictive factors. Results revealed that 40.4% of respondents were anemic. Pregnant women with an interpregnancy interval of less than 24 months were more likely to experience anemia compared to those with an interval of 24 months or more (p = 0.002). In addition, poor adherence to IFA tablet consumption was strongly associated with a higher prevalence of anemia (p<0.001). Logistic regression confirmed both interpregnancy interval and IFA adherence as significant predictors of anemia. Maintaining an optimal interpregnancy interval and improving adherence to IFA supplementation are critical strategies to prevent anemia during pregnancy.